A Green's Function Approach for Dynamic Stress Analysis of Spherical Shell under the Isotropic Impact Load. (3rd December 2015) - Lv, Jincheng; Zhang, Shike; Yuan, Xinsheng
Abstract : A Green's function approach is developed for the analytic solution of thick-walled spherical shell under an isotropic impact load, which involves building Green's function of this problem by using the appropriate boundary conditions of thick-walled spherical shell. This method can be used to analyze displacement distribution and dynamic stress distribution of the thick-walled spherical shell. The advantages of this method are able( 1 ) to avoid the superposition process of quasi-static solution and free vibration solution during decomposition of dynamic general solution of dynamics, ( 2 ) to well adapt for various initial conditions, and( 3 ) to conveniently analyze the dynamic stress distribution using numerical calculation. Finally, a special case is performed to verify that the proposed Green's function method is able to accurately analyze the dynamic stress distribution of thick-walled spherical shell under an isotropic impact load.